In vitro evaluation of the effects of yttria–alumina–silica microspheres on human keratinocyte cells1. Issue 2 (10th August 2012) - Radu, T.; Chiriac, M. T.; Popescu, O.; Simon, V.; Simon, S.
Abstract: The behavior of yttria–alumina–silica spray‐dried microspheres was investigated in vitro on a human keratinocyte cell line, first to exclude their cytotoxicity. The HaCaT cells were chosen due to their well‐characterized phenotype and their phagocytic ability. Microscopic analysis and cell viability tests showed no negative effect of the microspheres on cells morphology and behavior. Scanning electron microscopy and transmission electron microscopy results evidenced the cellular internalization of the microspheres at 48 h after their incubation with cultured cells. The shape, size distribution, structure, composition, and chemical states of the elements on samples surface were analyzed by SEM, transmission electron microscopy, x‐ray diffraction, and x‐ray photoelectron spectroscopy, because these properties could influence their internalization by cells. The yttrium distribution on the microspheres surface was indicated by fluorescence microscopy imaging. The microspheres dimension and shape inside the cells was in accordance with their dimension and shape before incubation. The microspheres seemed captured and engulfed by the cells in native form and appeared resistant to degradation over the first 48 h. Most of the analyzed cells took up more microspheres, suggesting that the microspheres were actively phagocytosed by the cells and accumulated within the cytoplasm. X‐ray photoelectron spectroscopy results on Al and Si atomic environments denoted Al–O–Si crosslinks, which improve the surface protection to corrosion. © 2012 Wiley Periodicals, Inc. J Biomed Mater Res Part A, 2013.